2021
DOI: 10.1002/adfm.202100251
|View full text |Cite
|
Sign up to set email alerts
|

Supplementary Networking of Interpenetrating Polymer System (SNIPSy) Strategy to Develop Strong & High Water Content Ionic Hydrogels for Solid Electrolyte Applications

Abstract: To synthesize hydrogels that possess tensile strength and modulus together in MPas along with extensibility at high equilibrium water content (≥90 wt%) is challenging but important from the application perspective. Especially, such hydrogel compositions are useful for fabricating flexible electronics devices for subsea applications, where underwater risk‐free implementation and optimum device performance at low temperature (≈0 °C) and high hydrostatic pressure (≤20 bar) conditions is desirable. The high water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 67 publications
0
28
0
Order By: Relevance
“…Notably, the overall performance of GPHE is also one of the best among representative research on zinc ion gel electrolytes over the past 3 years ( Fig. 2I and table S3) ( 7 , 21 23 , 25 , 31 , 34 , 35 ).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Notably, the overall performance of GPHE is also one of the best among representative research on zinc ion gel electrolytes over the past 3 years ( Fig. 2I and table S3) ( 7 , 21 23 , 25 , 31 , 34 , 35 ).…”
Section: Resultsmentioning
confidence: 93%
“…PVA-GO hydrogels were prepared via freeze-thawing treatments three times; subsequently, ZnSO 4 /MnSO 4 was introduced into the PVA-GO hydrogel host via a solution-soaking treatment ( Fig. 2B ) ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…To reinforce the hydrogel electrolyte without decreasing water content, Mandal et al developed an interpenetrating polymer system (IPS) as the supplementary network of PAM hydrogel electrolytes. 92 The IPS was composed of the crosslink between polyacryloyl hydrazide (PAHz) and poly(2-acrylamido-2-methyl-1-propanesulfonic acid) (PAMPS), which are capable of retaining high water content. Despite a high water content (87 wt%), the PAHz-AMPS-PAAm hydrogel electrolyte showed a high Young's modulus of 1.67 MP and an ultimate tensile strength of 2.1 MPa (Figure 6G), indicating the high mechanical strength of the hydrogel electrolyte reinforced by the IPS.…”
Section: Boosting Mechanical Strengthmentioning
confidence: 99%
“…(G) Effect of PAHz repeating unit (CONHNH 2 ) mol% on the σT, elongation at break, and G values. Reproduced with permission: Copyright 2021, Wiley 92 . (H) Synthesis schematic of the preparation of a CT3G30 hydrogel electrolyte (C, T, 3, G, and 30 represent cellulose, TEOS, the milliliters of TEOS added, glycerol, and the milliliters of glycerol added, respectively).…”
Section: Recent Progress In Famibsmentioning
confidence: 99%
“…Based on a polyacrylonitrile hydrogel dispersed with piezoelectric poly(vinylidene fluoride), Fu et al reported a self-powered hydrogel where the β-phase PVDF showed electrical signal response to strain change triggered by human activities. In recent years, galvanic-cell-based soft sensors have attracted a lot of research interest 51–54 due to the stable open circuit voltage upon large compressional strain 55 along with a scalable and facile fabrication strategy of multistimuli responsiveness. 56 Nevertheless, these self-powered soft sensors are unable to accurately detect tiny mechanical or environmental fluctuations in scalable applications where high sensitivity is required.…”
Section: Introductionmentioning
confidence: 99%